NEW UZBEKISTAN: DEVELOPMENT OF LIFESTYLE AND THE HUMAN FACTOR - Karimova Muyassarkhon Abdukayumovna (Modern American Journals, 2025)
In the era of rapid transformation and modernization, the Republic of Uzbekistan has embarked on a bold journey toward building a new model of national development - widely recognized as the “New Uzbekistan.” This concept reflects a comprehensive vision for societal progress rooted in democratic reforms, economic liberalization, and an unwavering focus on the human factor as the cornerstone of all policy and institutional change.